Nuclear receptors: transcriptional functions - Weigel, Nancy; McKenna, Neil (Henry Stewart Talks, 2007)
Introduction to transcription factors, Nuclear receptors as ligand-dependent transcription factors, Classes of nuclear receptor, Nuclear receptor ligands: agonists and antagonists, Nuclear receptor phylogeny, Nuclear receptor isoforms, The nuclear receptor DNA-binding domain, Hormone response elements, The nuclear receptor ligand-binding domain, Nuclear receptor mechanism, Subcellular localization of nuclear receptors, The effect of ligand binding, Nuclear receptor coregulators, Initial discoveries of coregulators, The SRC/p160 coregulator family, Nuclear receptor-coregulator interaction motifs, Histone acetylation and chromatin structure, The Nuclear Receptor Signaling Atlas (NURSA), Chromatin immunoprecipitation as a tool in nuclear receptor mechanism, Functional differences between type I and type II nuclear receptors, The coregulator exchange, DNA-binding independent functions, Transrepression, The role of kinases
Archived at 2020/08/13